Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1177/1087057113497798
|View full text |Cite
|
Sign up to set email alerts
|

An Isogenic Cell Panel Identifies Compounds That Inhibit Proliferation of mTOR-Pathway Addicted Cells by Different Mechanisms

Abstract: The mTOR pathway is a critical integrator of nutrient and growth factor signaling. Once activated, mTOR promotes cell growth and proliferation. Several components of the mTOR pathway are frequently deregulated in tumors, leading to constitutive activation of the pathway and thus contribute to uncontrolled cell growth. We performed a high-throughput screen with an isogenic cell line system to identify compounds specifically inhibiting proliferation of PTEN/mTOR-pathway addicted cells. We show here the character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Although mTORC1 activity is also increased in the Pten deficient cell lines (at threonine 389 of the mTORC1 target S6K), we previously showed that these cells are addicted to mTORC2 and not mTORC1 signaling for growth and survival [3]. An alternative route of in vitro transformation in this system is expression of the bcr-abl oncoprotein in 15V4 cells to generate IL3 independent b-abl cells ( Fig 1A) [6]. Unlike the Pten deficient cell lines, b-abl cells have similar basal levels of mTORC2 activity as the parental cells and a slight increase in mTORC1 signaling ( Fig 1B).…”
Section: In Vitro Transformation Of Mast Cellsmentioning
confidence: 83%
See 1 more Smart Citation
“…Although mTORC1 activity is also increased in the Pten deficient cell lines (at threonine 389 of the mTORC1 target S6K), we previously showed that these cells are addicted to mTORC2 and not mTORC1 signaling for growth and survival [3]. An alternative route of in vitro transformation in this system is expression of the bcr-abl oncoprotein in 15V4 cells to generate IL3 independent b-abl cells ( Fig 1A) [6]. Unlike the Pten deficient cell lines, b-abl cells have similar basal levels of mTORC2 activity as the parental cells and a slight increase in mTORC1 signaling ( Fig 1B).…”
Section: In Vitro Transformation Of Mast Cellsmentioning
confidence: 83%
“…Derivation of 15V4, 6.5, 6.8 and shP cells has been previously described [3]. b-abl cells were obtained by expressing a bcr-abl construct in 15V4 and selecting for IL3 independence [6]. Murine mast cell medium was supplemented with mouse IL3 from conditioned medium as previously described [3].…”
Section: Cell Culturementioning
confidence: 99%